Constitutional reform of Ukraine in 2016 and its impact on the development of the legal system - L. L. Goncharenko (Bulletin of Kharkiv National University of Internal Affairs)
It has been established that the constitution is the fundamental law of any modern state, which ensures the integrity of the country's legal system. The said legal act contains the most important provisions defining the basic guarantees for the protection of rights, freedoms and interests of a person and a citizen, as well as the key principles of functioning of the State as a whole and its legislative, executive and judicial branches. It is noted that the priority of the constitutional provisions is due to the fact that all other legal acts of different legal force are developed in accordance to it.